Spectrum of Paediatric Malignancies - Faisal Raza Malik , Awais Tahir, Huma Bashir, Parveen Akhtar (Journal of Rawalpindi Medical College, 2012)
Background: To find out the spectrum of childhood malignancies Methods: In this descriptive study all children under 12 years, admitted at Fauji Foundation Hospital Rawalpindi, with confirmed diagnosis of any malignancy by means of histological or cytological examinations were included. Results: Out of 81 cases of malignancies forty two (51.9%) were between 5-9 years of age, 20(24.7%) were 0-5 years of age and 19(23.5%) were 9-12 years of age. The frequency of paediatric malignancies was found to be higher among boys (66.7%). Leukemia (54.3%) was the commonest followed by Lymphoma (23.5%) and Wilm’s tumor (8.6%). Conclusion: Peak age incidence for malignancies is 5-9 years (51.5%). The most common malignancy in age group 0-5 years is Wilm’s tumor (6.2%) while ALL is common in age groups 5-9 years and 9-12 years (30.9% and 9.9% respectively)